Compartment‐specific effects of muscle strength on bone microarchitecture in women at high risk of osteoporosis. Issue 5 (18th July 2022) - Simon, Alexander; Schäfer, Hannah S.; Schmidt, Felix N.; Stürznickel, Julian; Amling, Michael; Rolvien, Tim
Abstract: Background: It is well known that skeletal integrity is influenced by the musculature. Poor muscle strength (i.e. sarcopenia) is considered a major predictor of fragility fractures. While this observation appears particularly relevant for older women with increased risk of osteoporosis, there has been no comprehensive investigation to determine the influence of muscle performance on compartment‐specific bone microarchitecture in multiple body regions. Methods: We retrospectively analysed data from different muscle performance and bone microarchitecture assessments in 230 women (aged 21 to 87 years) at high risk of osteoporosis. Muscle performance tests included grip strength and chair rising test (CRT) combined with mechanography. Balance was determined by Romberg posturography. Areal bone mineral density (BMD) was measured by dual‐energy X‐ray absorptiometry (DXA) at the hip and lumbar spine. Compartment‐specific volumetric BMD, microarchitecture, and geometry were assessed by second‐generation high‐resolution peripheral quantitative computed tomography (HR‐pQCT) at multiple skeletal sites (distal radius, tibia, and fibula). Regression models were applied to test for interactions between muscle and bone parameters. Subgroups were defined to compare women with osteoporosis and osteosarcopenia regarding BMD and microarchitecture. Results: While osteoporosis was diagnosed in 115/230 (50.0%) women, sarcopenia was detected in 38/230 (16.5%). Positive associations of both grip strength and CRT maximum force with cortical geometric and microarchitectural parameters were detected at all measured sites, with the strongest effect applying to CRT maximum force and tibial parameters (e.g. tibial cortical area R 2  = 0.36, P  < 0.0001, and tibial cortical thickness R 2  = 0.26, P  < 0.0001). Balance parameters showed much weaker or no associations with HR‐pQCT parameters. Major associations between muscle strength and trabecular parameters could not be confirmed. Age and body mass index were confirmed as negative and positive predictors for several microarchitectural parameters, respectively. An independent predictive value of grip strength on radial, tibial, and fibular (all P  < 0.01) cortical area and of CRT maximum relative force on cortical thickness (all P  < 0.05) was revealed. Women with osteosarcopenia showed significantly reduced cortical HR‐pQCT parameters but no differences in DXA values compared with women with osteoporosis but no sarcopenia. Stratification by fracture and treatment status revealed that vertebral fractures and denosumab treatment altered the muscle–bone interaction. Conclusions: A systemic interaction between muscle strength and bone microarchitecture was demonstrated, and this interaction appears to be primarily with the cortical bone compartment. The value of muscle assessments in fracture risk evaluation may be partly mediated by their effects on bone microarchitecture.